2017
DOI: 10.5535/arm.2017.41.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome and Factors Affecting Prognosis of Extracorporeal Shockwave Therapy for Chronic Refractory Achilles Tendinopathy

Abstract: ObjectiveTo investigate the factors affecting prognosis of extracorporeal shockwave therapy (ESWT) for chronic refractory Achilles tendinopathy (AT).MethodsThirty-six patients (48 consecutive feet) with chronic AT (>6 months) and who underwent ESWT for ‘poor’ or ‘fair’ grade in Roles-Maudsley Score (RMS) after unsuccessful conservative treatment were included in the present study. A maximum of 12 sessions of ESWT were conducted until treatment success: RMS reached ‘good’ or ‘excellent’. Termination of ESWT for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
(64 reference statements)
1
18
0
4
Order By: Relevance
“…Lee et al investigated the long-term outcome and factors affecting the prognosis of ESWT for chronic refractory Achilles tendinopathy [37]. Immediate treatment success was associated with an absence of a retrocalcaneal enthesophyte on X-ray, presence of pretreatment abnormal ultrasonography echogenicity, shorter mean duration of "posttreatment soreness," and shorter duration of "posttreatment soreness after first ESWT."…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al investigated the long-term outcome and factors affecting the prognosis of ESWT for chronic refractory Achilles tendinopathy [37]. Immediate treatment success was associated with an absence of a retrocalcaneal enthesophyte on X-ray, presence of pretreatment abnormal ultrasonography echogenicity, shorter mean duration of "posttreatment soreness," and shorter duration of "posttreatment soreness after first ESWT."…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies regarding usage of ESWT in patients with chronic Achilles tendinopathy reported short-term 3 or 4 months [ 10 ], 6 months [ 14 ] or long -term 12 months outcome [ 10 ] [ 11 ] [ 12 ]. We used low - energy radial extracorporeal shock wave therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the reported studies, Rompe et al treatment protocol included 3 sessions of low - energy ESWT using 0.12 mJ/mm 2 with 2,000 shocks per session [ 10 ], Pavone included 4 sessions of low -energy ESWT with a 2 - week interval, from 800 shocks in each one (4 Hz, 14 KeV) [ 11 ]; Lee et al included a maximum of 12 sessions of ESWT (0.10 -0.11 mJ/mm 2 , 600 shocks, weekly) were conducted until Roles - Maudsley Score reached ‘good’ or ‘excellent’ (treatment success), [ 12 ]; while Furia performed just a single session of ESWT using high -energy (0.21 mJ/mm 2 ) with 3,000 shocks [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations